Functional characterization of Francisella tularensis subspecies holarctica genotypes during tick cell and macrophage infections using a proteogenomic approach - Schütz, Sara Doina; Brackmann, Maximilian; Liechti, Nicole; Moser, Michel; Wittwer, Matthias; Bruggmann, Rémy (Frontiers in Cellular and Infection Microbiology, 2024)
Tularemia is a vector-borne disease caused by the Gram-negative bacterium Francisella tularensis. Known hosts and vectors in Europe are hare and ticks. F. tularensis is transmitted from ticks and animals, but also from the hydrotelluric environment and the consumption of contaminated water or food. A changing climate expands the range in which ticks can live and consequently might contribute to increasing case numbers of tularemia. Two subspecies of F. tularensis are human pathogenic. Francisella tularensis tularensis (Ftt) is endemic in North America, while Francisella tularensis holarctica (Fth) is the only subspecies causing tularemia in Europe. Ft is classified as a category A bioterrorism agent due to its low infectious dose, multiple modes of transmission, high infectivity and potential for airborne transmission and has become a global public health concern. In line with the European survey and previous phylogenetic studies, Switzerland shows the co-distribution of B.6 and B.12 strains with different geographical distribution and prevalence within the country. To establish itself in different host environments of ticks and mammals, F. tularensis presumably undergoes substantial changes on the transcriptomics and proteomic level. Here we investigate the transcriptomic and proteomic differences of five strains of Fth upon infection of rabbit macrophages and tick cells.